ANALISIS KEPUASAN PENGHUNI RUMAH SUBSIDI DI TANGERANG - Saputra, Handarta Dedy; .Tobing, Fenny B.N.L.Tobing; Siagian, Jonny (Fundamental Management Journal, 2017)
The purpose of this study to determine the level of satisfaction of the household type in Griya Permata Cisoka Tangerang toward building attributes based on performance and interest. Respondent were selected using formula slovin, a population of 743 household, while respondents consisted of 88 families. Data have been collected were analyzed using performace importance and cartesian diagram. The research analyzed using 12 attributes are available on the five dimensions of Tangibles, Reliability, Responsiveness, Assurance and Emphaty. Satisfaction research result of the household type 22 in Griya Permata Cisoka Tangerang to attribute indicates the cartesian diagram mostly in the B quadrant in which the performance of the company has been in accordance with the desire of residents have said to be very satisfied. Keyword: Satisfaction, importance, performance